IMPLEMENTASI KEBIJAKAN TENTANG BANTUAN STIMULAN PERUMAHAN SWADAYA (BSPS) DI KECAMATAN BATUMANDI KABUPATEN BALANGAN (STUDI KASUS DI DESA BANUA HANYAR DAN HAMPARAYA) - Norsanti; Mariyatul Fitriah (stiatabalong.ac.id, 2022)
Self-help Housing Stimulant Assistance (BSPS) is one of the government's programs through the Minister of Public Works and Public Housing to improve the community's ability to access decent housing. The research method used in this research is descriptive with a qualitative approach. Data were collected through interviews, observations and documentation with the research subjects, namely policy implementers and the recipients of the BSPS program. The results of the study illustrate that the Self-Help Housing Stimulant Assistance program has been running, although there are still poor people who have not received assistance due to the limited budget from the government, but this program has a positive impact on the people who receive assistance. The result of the implementation of this policy is that underprivileged people can access decent housing by utilizing the assistance provided by the government. The supporting factors for the implementation of the policy on Self-Help Housing Stimulant Assistance in Batumandi Sub District are program objectives that are in line with the needs of low-income communities and support from the political elite while the inhibiting factors for implementing this policy are socialization to the community that has not run optimally, the limited time for implementing the BSPS and the limited quota of BSPS recipients.